A influência do ready-made na escultura moderna - Ribeiro, Carlos Frederico Botão D’Alincourt, 1969- (2016)
The work produced by Marcel Duchamp revolutionized and redirected the path of the Visual Arts, allowing vast and numerous developments for artists and their creations. Under his influence, several changes came quickly and sequentially in many avant-garde movements and their transgressive and libertarian effects can be noticed in the artistic achievements over the past century and in contemporary times. This text intends to contribute to the quest for understanding a little better the relationship between Duchamp’s readymades and their influx, their parallel and consequences in the universe of sculpture. On the basis of information provided by the author and leading experts, covering the primary context for the second half of the 20th century, this research aims to address some unique aspects of the “duchampian” object as against or/in favor of sculpture. Although we have a wide perception of the groundbreaking and insurgent thoughts of Marcel Duchamp, his directions, proposals and intentions, it is relevant the need of an analysis of the readymade under the sculptural bias, as a three-dimensional conceptual object offered as opposing a three-dimensional “retinal” object and its impact as beneficial to Sculpture and, therefore, to Art